Transformasi Fungsi LinkedIn sebagai Alat Personal Branding dalam Ekosistem Profesional Digital Studi Kasus pada Generasi Z di Indonesia dan Jerman - Ramadhiansyah, Dimas; Sembada, Deo Agung; Madyson Soekah, Jonathan (Airlangga University, 2025)
This study examines the transformation of LinkedIn’s function within the digital professional ecosystem and its impact on Generation Z in Indonesia and Germany. As digital natives, Generation Z increasingly uses LinkedIn not only as a job-searching tool but also as a medium for personal branding to build a professional image, enhance visibility, and expand networks. Using in-depth interviews with eight active LinkedIn users, the study reveals that in Indonesia, LinkedIn has evolved into a strategic platform for personal branding and professional networking. The platform’s algorithm, which emphasizes organic interaction, enables Generation Z to strengthen their professional identity through knowledge sharing and community engagement. However, algorithmic changes also present challenges, such as the dominance of personal content over job postings and the appearance of global content that may be less relevant to local job seekers. Meanwhile, Generation Z in Germany faces difficulties balancing authenticity with professionalism when shaping their digital identity. The findings highlight that successful personal branding on LinkedIn requires a strategic approach, including profile optimization, active engagement with relevant content, and maintaining a balance between professional and personal life. Thus, LinkedIn functions not only as a career tool but also as a space for identity construction among young generations across countries.